Homeopathic Management of Warts Based on its Shape and Location (Homoeopathy for All, 2024)
The skin, which is frequently referred  to as the "mirror of the soul," is a  reflection of both our internal and  external health. This principle is  the cornerstone of the homeopathic  treatment of cutaneous abnormalities,  such as warts, moles, etc. Warts  are prevalent skin growths that can  manifest on a variety of body regions,  including the palms, feet, and mucous  membranes, as a result of an infection  with the human papillomavirus  (HPV). They are classified according  to their location—common warts  around nails and digits, foot warts,  and genital warts—as well as their  morphology and texture, which can  be fuzzy, firm, flat, smooth, scratchy,  or leathery. These growths are highly  contagious and can be transmitted  through direct cutaneous contact  or indirectly through contaminated  surfaces. In the Indian context, warts  hold particular cultural and medical  significance, with various beliefs and  myths influencing their perception and  treatment.
Keywords: socio-economic; attribute; furuncles